The Political Economy of Natural Disaster Insurance: Lessons from the Failure of a Proposed Compulsory Insurance Scheme in Germany - Reimund Schwarze; Gert G. Wagner (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
This paper studies the politico-economic reasons for the refusal of a proposed compulsory flood insurance scheme in Germany. It provides the rationale for such scheme and outlines the basic features of a market-orientated design. The main reasons for the political down-turn of this proposal were the misperceived costs of a state guarantee, legal objections against a compulsory insurance, distributional conflicts between the federal government and the German states (Länder) on the implied administrative costs, and the well-known charity hazard of ad-hoc disaster relief. The focus on pure market solutions proved to be an ineffective strategy for policy advice in this field. – – Dieses Papier untersucht die politisch-ökonomischen Gründe für die Ablehnung einer Versicherungspflicht für Elementarschäden in Deutschland. Nach einer Darlegung der ökonomischen Vorteilhaftigkeit und der Grundzüge eines praktikablen Modells einer Elementarschadenversicherungspflicht werden die drei wichtigsten Argumente der Kritiker diskutiert. Dies sind zu einem die Notwendigkeit und Höhe einer staatlichen Ausfalldeckung, rechtliche Bedenken gegen eine Beschränkung der Konsumentensouveränität und Verteilungskonflikte zwischen Bund und Ländern auf der Grundlage unterschiedlicher Gefahrenexposition sowie die politisch-ökonomische Rationalität von Soforthilfemaßnahmen. Die ökonomische Forderung nach einer reinen Marktlösung erwies sich in den Verhandlungen als ein Nirwana-Ansatz.
Keywords: 330; Elementarschadenversicherung; Versicherungspflicht; Public Choice; Deutschland